Signs of Variation and Change in The System of Nominal Classification in Bribri - Sánchez Avendaño, Carlos (2020)
In this article we analyse the signs of variation and change of the nominal classification system in Bribri. In this language, nouns are assigned to nominal classes related to parameters such as the shape of the referent (flat, round, long) or its human character, among others. The class is realized by means of suffixes attached to the numeral roots, therefore it has been conceived as a system of numeral classifiers. However, the paradigms show formal differences up to certain numbers. For this reason, it has been suspected that, due to the shift process of the language, some classes have lost their own marking in some cases. In order to evaluate this hypothesis, we turned to the oldest descriptions and discursive corpus. In addition, we collected current date on the linguistic competence of several speakers. The examination of the historical documentation shows that the paradigms have not lost their marking since the end of the 19th century. On the other hand, the current data show that the tendency of change linked to the shift process consists of extending the marking of the flat class to others.